AfricArXiv - the pan-African Open Access Portal - Havemann, Jo (My University, 2023)
This presentation was delivered at Open Repositories 2023 Conference as part of Panel 5: Supporting Trusted OA Usage Data Reporting and Analytics through Shared Infrastructure.
Keywords: Pan African; Open Access; Scholarly Infrastructure